Openness, inequality and poverty : endowments matter - Gourdon, Julien; Maystre, Nicolas; Melo, Jaime de. (Torino : Centro Studi Luca D'Agliano, 2008)
"Using tariffs as a measure of openness, the authors find consistent evidence that the conditional effects of trade liberalization on inequ ality are correlated with relative factor endowments. Trade liberaliza tion is associated with increases in inequality in countries well-endow ed in highly skilled workers and capital or with workers that have very low education levels and in countries relatively well-endowed in minin g and fuels. Trade liberalization is associated with decreases in ineq uality in countries that are well-endowed with primary-educated labor. Similar results are also apparent when decile data are used instead of the usual Gini coefficient. The results are strongly supportive of th e factor-proportions theory of trade and suggest that trade liberalizat ion in poor countries where the share of the labor force with very low education levels (likely employed in nontradable activities) is high ra ises inequality. In the sample, countries with low education levels al so have relatively scarce endowments of capital. Quantitatively capita l scarcity is the dominating effect so that trade liberalization is acc ompanied by reduced income inequality in low-income countries. Within- country inequality is also positively correlated with measures of macro economic instability. Simulation results suggest that relatively small changes in inequality as measured by aggregate measures of inequality like the Gini coefficient are magnified when estimates are carried out using decile data. "--World Bank web site.
Sponsored by Banca D'Italia- Roma Fondazione Cassa Di Risparmio Di Torino.
Keywords: Free trade; Income distribution; Equality